Pengaruh Permainan Playdough terhadap Kemampuan Keaksaraan Awal Anak Usia 4-5 Tahun - Zuhrotun Nisa (Universitas Muhammadiyah Gresik, 2021)
The purpose of this study was to examine the effect of playdough on early literacy skills of children aged 4-5 years at TK Muslimat NU 5 Hidayatus shibyan Sukomulyo manyar Gresik. And this research is motivated by the early literacy ability of the children of the A2 TK Muslimat NU 5 Hidayatus Shibyan Sukomulyo Manyar Gresik group, which can be said to be still low. The results obtained by early researchers in the observation activity called the pre-test activity showed that children began to connect the symbol of the word vehicle with the image of the vehicle, and had not been able to scribble on the names of their parents and began to imitate the letters in the word vehicle. Therefore, the researcher assumes that early literacy skills can be categorized as not yet well developed. The method used in this research is a quantitative research method which is included in the Pre Experimental Design research type with a research design of